Ultrasonic application and spray drying during amorphous calcium phosphate synthesis - Chanfrau, Jorge E. Rodriguez [UNESP]; Pantoja, Yaymarilis Veranes; Guastaldi, Antonio Carlos [UNESP] (AMG Transcend Association, 2019)
Hydroxyapatite, amorphous calcium phosphates, calcium triphosphate and calcium octaphosphate are the main components present in bones and teeth. Calcium phosphates are easily synthesized, playing an important role in regenerative medicine, being able to be used as bone implants. There are different ways of synthesizing phosphates, the most commonly used being wet chemical method. The objective of this work was to study the influence of the use of ultrasound and spray drying on the synthesis of amorphous calcium phosphate. Two synthetic variants were studied. One without ultrasound application and the other with ultrasound application. The samples obtained were characterized by X-ray diffraction, FTIR spectroscopy and scanning electron microscopy. The particle size by electron microscopy and the calcium content by atomic absorption was determined. The results showed that when spray drying is applied, particle sizes of less than 261 nm are obtained in the samples synthesized without ultrasound application, being less than 59 nm in the samples synthesized with ultrasound application. The statistical analysis by ANOVA showed significant differences between the particle sizes of the samples synthesized without ultrasound application and the samples synthesized by applying ultrasound. In both cases the particles were spherical. The results obtained show that the application of ultrasound during the synthesis process decreases the particle size, increasing the surface area, which favors the spray drying process.
Keywords: Amorphous calcium phosphate; Biomaterials; Particle size; Spray drying